Questionnaire based survey on practicing OTC antimicrobials among 1st and 2nd year medical student of RIMS in Ranchi, India - Ranjeeta, Kumari; Anil, Pawan Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: OTC (over the counter) drugs are defined as “Drugs available freely on the counter without prescription of a registered medical practitioner The WHO has also pointed out that responsible self-medication can help prevent and treat ailments that do not require medical consultation and provides a cheaper alternative for treating common illnesses. Studies have also found that educated people have a greater tendency to practice self-medication than illiterates. several studies have been carried out in different populations to evaluate the practice of self-medication there is a paucity of studies on self medication of antimicrobials among medical students. Methods: This was a questionnaire based study of one months duration. A prevalidated questionnaire was distributed to 258 students, to assess practice of otc anti-microbials in 1st (2nd semester) and 2nd (5th semester) year medical undergraduate students of Rajendra Institute of Medical science, Ranchi. Results: The results of this study showed that out of 258 students 208 (80.6%) students used antimicrobials as OTC. Out of 258 from both the year, 225 students had knowledge about OTC anti-microbials drug. Most common reason for practicing OTC anti-microbials was the minor ailment 86 (41.3%). Again most common indication was diarrhea 69 (33.3%). In this study we observed that the most common source of information regarding OTC anti-microbials were senior students 63 (30.4%) and most commonly used anti-microbials as self-medication were ciprofloxacin 92 (44.3%). Conclusions: This study highlights the very high prevalence of OTC anti-microbials use among medical students, inappropriate use due to the lack of knowledge. At the higher i.e. policy-making level, there is an urgent need to legislate and enforce laws which can restrict access to the supply of medicines without prescription by pharmacies and strict rules regarding pharmaceutical advertising. Again, there is a need for an impactful public enlightenment campaign to educate the people about the disadvantages and life-threatening complication of Otc anti-microbials. And at last emphasis should be given on rationalized use of anti-microbials.